Ethyl Silicate for Unbaked Earth Tablets Conservation: Evaluation of the Physico-mechanical Aspects. (3rd July 2020) - Tiennot, Mathilde; Mertz, Jean-Didier; Bourgès, Ann; Liégey, Anne; Chemmi, Atika; Bouquillon, Anne
ABSTRACT: Preservation of cuneiform tablets made with clay minerals is an ongoing conservation issue. A treatment based on TEOS consolidation has been used since 1996 at the Louvre museum. The characterization of the tablets pointed out kaolinite, illite, and smectite as the three main clay minerals constituting the objects. In this research, the physico-mechanical aspects of the treatment are investigated. The penetration depth of the TEOS solution and the gradient induced are quantified using laboratory samples. TEOS treatment preserves the macroscopic swelling and the vapour transfer properties, but modifies the clay's affinity to moisture. Elastic properties are gradually improved for all clays, but only kaolinite's strength increases significantly. The impact of TEOS treatment on the natural behaviour related to the respective structure of the clays is considered, and the amount of kaolinite required to create adequate reactions appears to be of interest for conservation treatments.